A case of multiple evanescent white dot syndrome misdiagnosed as optic neuritis: Differential diagnosis for the neurologist - Pellegrini, Francesco (J Neurosci Rural Pract, 2016)
A 25-year-old female presented to a local hospital for acute onset of a central scotoma in the left visual field. She was visited by the neurologist, and a diagnosis of left retrobulbar optic neuritis was made. Magnetic resonance imaging scan was normal. Ophthalmic examination revealed a multiple evanescent white dot syndrome. After a description of the case, a brief differential diagnosis between these two entities is made. The neurologist should be aware of this uncommon condition.